THE ESSENCE AND FEATURES OF LABOR SOCIOLOGY - Bakhromjon Nomanjanov (Journal Park Publishing, 2023)
The question of studying new social relations and their features, the process of transition to market relations and its future social consequences, the aspects of Labor Relations in the new conditions, which are currently taking shape in the field of Social Sciences, in particular before the science of “sociology”, is transitory. Sociology and its maxcyc theory - within the framework of Labor sociology, both theoretical and practical aspects of these problems should be considered in a dialectical way. All aspects, processes of the life of society associated with labor activity are studied on the basis of a specific sociological study.
Keywords: labor, labor sociology, society, entrepreneurship, production, labor productivity.